Determining the Relationship Between Interpersonal Mindfulness, Social Media Use, and Marital Satisfaction - Riahifar , Maryam; Abdollahi, Abbas; Vakili , Samira (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to determine the relationship between interpersonal mindfulness, social media use, and marital satisfaction. Methods and Materials: This research is an applied study in terms of its objective. Additionally, it is a field study regarding data collection and analysis methods. The population under investigation consisted of married residents of Tehran who are members of social networks. Simple random sampling was employed for sample selection. To estimate the sample size, the formula proposed by Tabachnick and Fidell (2007) was utilized, resulting in a required sample size of 106 participants. In this study, data were collected using the Interpersonal Mindfulness Questionnaire (IMQ) (Paucho et al., 2018), the Social Networks Questionnaire (Khwaja Ahmadi, Pouladi, & Bahraini, 2016), and the ENRICH Marital Satisfaction Scale. To assess the structural model of the research, the four-stage structural model evaluation proposed by Hair et al. (2017) was applied. Findings: The results of the covariance analysis test indicated that interpersonal mindfulness has a positive relationship with marital satisfaction, whereas social media use has a negative relationship with marital satisfaction. Conclusion: Given the significant relationship between interpersonal mindfulness and social media use with marital satisfaction, it is recommended to design programs to enhance interpersonal mindfulness and appropriate social media use for increasing marital satisfaction among couples and implement these through virtual and electronic workshops.